2020
DOI: 10.1038/s41598-020-67415-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the amino acid position controlling the different enzymatic activities in walnut tyrosinase isoenzymes (jrPPO1 and jrPPO2)

Abstract: Polyphenol oxidases (PPOs) are ubiquitously distributed among plants, bacteria, fungi and animals. They catalyze the hydroxylation of monophenols (monophenolase activity) and the oxidation of o-diphenols (diphenolase activity) to o-quinones. PPOs are commonly present as an isoenzyme family. In walnut (Juglans regia), two different genes (jrPPO1 and jrPPO2) encoding PPOs have been identified. In this study, jrPPO2 was, for the first time, heterologously expressed in E. coli and characterized as a tyrosinase (TY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…However, samples from the V treatment did not react with protocatechuic acid or L-tyrosine, which indicated a low level of PPO activity. Compared with JrPPO2, JrPPO1 exerts greater activity towards monophenols and does not accept protocatechuic acid as substrate, whereas JrPPO2 is more active towards o -diphenols [ 30 ]. Therefore, our results suggest that there is high JrPPO2 activity under treatment A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, samples from the V treatment did not react with protocatechuic acid or L-tyrosine, which indicated a low level of PPO activity. Compared with JrPPO2, JrPPO1 exerts greater activity towards monophenols and does not accept protocatechuic acid as substrate, whereas JrPPO2 is more active towards o -diphenols [ 30 ]. Therefore, our results suggest that there is high JrPPO2 activity under treatment A.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether JrPPO1 or JrPPO2 exerted high activity in different stages or tissues, a simple browning assay was performed essentially as described by Panis [ 30 ]. Total protein (via a supernatant) was isolated from equal weights of explants or different tissues as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a mechanism for the hydroxylation by Ao CO4 has been proposed, where the enzyme’s copper site is in hydroperoxide -form and monooxygenation occurs by electrophilic aromatic substitution without the need for deprotonation (5). Recently, docking studies revealed that the preference towards diphenolic substrates, exhibited by PPOs bearing a Gly in position H B1 +1, is explained by a “laying down” orientation of the substrate, which is stereochemically prohibited in PPOs bearing a bulkier Asn residue (15).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of various crystallographic and molecular docking studies, the structural determinants that affect the distinction between the two enzymatic activities and the substrate specificity exhibited by PPOs are still not fully understood. For instance, molecular studies on two walnut (Juglans regia) tyrosinase isoenzymes (JrPPO1 and JrPPO2) showed that the activity towards monophenolic substrates was dependent on the occurrence of an asparagine residue located after one of the CuB coordinating histidines [11]. However, there are many PPOs that do not have an Asn residue in this position but still display monophenolase activity [7].…”
Section: Introductionmentioning
confidence: 99%